How perceived risk influences college students' preventive behavior: Novel data of COVID-19 campus lockdown from Wuhan, China - Zhang, Lanxing; Cheng, Xiaoyu; Li, Zhuangzhuang (Frontiers in Public Health, 2023)
Taking preventive behaviors is a key measure to protect people from infectious disease. Protection Motivation Theory (PMT) suggests that perceived risk motivates individuals to take protective measures. COVID-19 pandemic has posed unprecedented stress to the public, and changes in perceived risk may be more pronounced among college students than other groups due to the related campus lockdown. With 1119 college students recruited as research subjects, a quantitative research design was conducted in Wuhan, China, to find out the relationship between perceived risk and preventive behavior of college students, as well as the mediation effect of individual affect and the moderating effect of physical exercise. The results showed that the preventive behavior of college students was significantly affected by perceived risk, and positive affect and negative affect both played a mediating role between perceived risk and preventive behavior. Specifically, positive affect benefited to the relationship between perceived risk and preventive behavior, negative affect was detrimental to their relationship, and the mediation effect of positive affect is significantly higher than that of negative affect. Furthermore, physical exercise played a moderating role in the mediation effect of positive affect and of negative affect. Therefore, appropriate measures should be taken to strengthen Chinese college students' perceived risk and provide them with corresponding guidance. The importance of physical exercise should also be emphasized to help college students with low perceived risk reduce negative affect, increase positive affect and promote their preventive behavior.